Percutaneous Ethanol Injection in Combination with Laser Ablation for a 100 ml Partially Cystic Thyroid Nodule - Roberto Negro; Gabriele Greco (Case Reports in Endocrinology)
Until nonsurgical techniques like laser ablation (LA) or radiofrequency became available, patients suffering from large nodules with compressive symptoms were addressed to surgery. We describe the case of a 59-year-old woman with a large, partially cystic thyroid nodule having a volume of about 100 ml. As the patient refused surgery, despite her constant local discomfort, such large partially cystic nodule underwent several percutaneous ethanol injections (PEI) and then was submitted to LA. The combination of these two procedures allowed firstly complete disappearance of the cystic component and secondly a significant reduction of thyroid nodule, which finally measured 17 ml in volume (82% reduction compared to baseline). This case demonstrates that even in very large partially cystic nodules LA preceded by PEI represents a valid alternative to surgery.